2013
DOI: 10.1097/cad.0b013e32835c401c
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sorafenib-induced high-grade skin rash in Japanese patients with advanced renal cell carcinoma

Abstract: The aim of this study was to evaluate the clinical factors, drug-related genetic polymorphisms, and human leukocyte antigen (HLA) types to determine the association with sorafenib-induced high-grade skin rash (HGSR) in Japanese patients with advanced renal cell carcinoma (RCC). A total of 55 patients with advanced RCC treated with sorafenib were analyzed retrospectively. Of these, 33 patients were subjected to HLA typing and polymorphism analyses of CYP3A5, ABCB1, ABCC2, and UGT1A1, which are involved in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
19
1
Order By: Relevance
“…A recent study by Ikeda et al [7] revealed that the incidence of EM induced by sorafenib was higher (25%) than previous reports. Kodaira et al [8] and Tsuchiya et al [9] also reported that 19-22% patients experienced EM induced by sorafenib. It is possible, however, that the occurrence rate of toxic skin reactions such as EM and SJS might be different between Japanese people and white people.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ikeda et al [7] revealed that the incidence of EM induced by sorafenib was higher (25%) than previous reports. Kodaira et al [8] and Tsuchiya et al [9] also reported that 19-22% patients experienced EM induced by sorafenib. It is possible, however, that the occurrence rate of toxic skin reactions such as EM and SJS might be different between Japanese people and white people.…”
Section: Discussionmentioning
confidence: 99%
“…This has been validated for many agents in this group, including sorafenib, sunitinib, axitinib, and cabozantinib [16,[46][47][48][49]. Higher initial dose, initial dose per body weight, and initial dose per body surface area all result in a significant incidence of high-grade HFSR [50]. Moreover, Hilger et al [51] demonstrated that sorafenib-induced skin toxicity was associated with both maximal plasma concentration and area under the curve.…”
Section: Pharmacologic Risk Factorsmentioning
confidence: 97%
“…Only two pharmacogenetic studies on sorafenib were found in which genetic polymorphisms in ABCC2 and HLA-A were associated with high-grade skin rash and rs2071559 in VEGF-R2 was associated with PFS and OS. For axitinib, no associations were reported [40][41][42][43][44].…”
Section: Pharmacogenetics To Predict Pazopanib Efficacymentioning
confidence: 98%
“…In a study of 55 Japanese mRCC patients, Tsuchiya et al [43] reported that the CC genotype of rs717620 in ABCC2 compared to the CT genotype and the HLA-A*24 allele were both associated with an increased risk for sorafenib-induced high-grade skin rash. In 2015, Escudier et al [44] reported a set of 305 mRCC patients (n = 159 axitinib and n = 146 sorafenib), in which 15 SNPs were investigated in VEGF-A, VEGF-R1, VEGF-R2, and HIF-1A for the association with blood pressure or efficacy outcomes.…”
Section: Pharmacogenetics To Predict Clinical Outcome Of Sorafenib Ormentioning
confidence: 99%